Mitochondrial Fragmentation as a Key Driver of Neurodegenerative Disease - Chaplygina, Alina; Zhdanova, Daria (Current Alzheimer Research, 2024)
Mitochondrial form and function are intricately linked through dynamic processes of fusion and fission, and disruptions in these processes are key drivers of neurodegenerative diseases, like Alzheimer’s. The inability of mitochondria to transition between their dynamic forms is a critical factor in the development of pathological states. In this paper, we focus on the importance of different types of mitochondrial phenotypes in nervous tissue, discussing how mitochondria in Alzheimer's disease are “stuck” in certain patterns and how this pattern maintains itself. Understanding the specific roles and transitions between mitochondrial forms, including tiny, networked, and hyperfused, is crucial in developing new therapies aimed at restoring mitochondrial homeostasis. By targeting these dynamics, we may be able to intervene early in the disease process, offering novel avenues for preventing or treating neurodegeneration.
Keywords: Alzheimer' s disease